Combined Home Exercise Is More Effective Than Range-of-Motion Home Exercise in Patients with Ankylosing Spondylitis: A Randomized Controlled Trial. (7th September 2014) - Hsieh, Lin-Fen; Chuang, Chih-Cheng; Tseng, Ching-Shiang; Wei, James Cheng-Chung; Hsu, Wei-Chun; Lin, Yi-Jia
Abstract : Home exercise is often recommended for management of patients with ankylosing spondylitis (AS); however, what kind of home exercise is more beneficial for patients with AS has not been determined yet. We aimed to compare the effectiveness of combined home exercise (COMB) and range-of-motion home exercise (ROM) in patients with AS. Nineteen subjects with AS completed either COMB (n = 9 ) or ROM (n = 10 ) program. The COMB program included range-of-motion, strengthening, and aerobic exercise while the ROM program consisted of daily range-of-motion exercise only. After exercise instruction, subjects in each group performed home exercise for 3 months. Assessment included cardiopulmonary exercise test, pulmonary function test, spinal mobility measurement, chest expansion, Bath Ankylosing Spondylitis Functional Index (BASFI), and other functional ability and laboratory tests. After exercise, the COMB group showed significant improvement in peak oxygen uptake (12.3%, P = 0.008 ) and BASFI (P = 0.028 ), and the changed score between pre- and postexercise data was significantly greater in the COMB group regarding peak oxygen uptake and BASFI. Significant improvement in finger-to-floor distance after 3-month exercise was found only in the COMB group (P = 0.033 ). This study demonstrates that a combined home exercise is more effective than range-of-motion home exercise alone in aerobic capacity and functional ability.